2002
DOI: 10.1128/ec.1.4.583-593.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Class of Cargo Protein inTetrahymena thermophilaDense Core Secretory Granules

Abstract: Regulated exocytosis of dense core secretory granules releases biologically active proteins in a stimulusdependent fashion. The packaging of the cargo within newly forming granules involves a transition: soluble polypeptides condense to form water-insoluble aggregates that constitute the granule cores. Following exocytosis, the cores generally disassemble to diffuse in the cell environment. The ciliates Tetrahymena thermophila and Paramecium tetraurelia have been advanced as genetically manipulatable systems f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 53 publications
0
34
0
1
Order By: Relevance
“…Studies of two different members of this family in Tetrahymena, IGR1 (induced during granule regeneration 1) and GRT1 (granule tip 1), suggested that these proteins are functionally distinct from the spring-forming Grl proteins. First, whereas gene disruption of any of the highly transcribed GRL genes resulted in grossly aberrant spring formation, no such defect was seen upon disruption of IGR1 (16). However, this could be explained by the fact that IGR1 encodes a relatively low-abundance protein in DCGs, and furthermore its function could be redundant with that of the highly related gene, IGR2.…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Studies of two different members of this family in Tetrahymena, IGR1 (induced during granule regeneration 1) and GRT1 (granule tip 1), suggested that these proteins are functionally distinct from the spring-forming Grl proteins. First, whereas gene disruption of any of the highly transcribed GRL genes resulted in grossly aberrant spring formation, no such defect was seen upon disruption of IGR1 (16). However, this could be explained by the fact that IGR1 encodes a relatively low-abundance protein in DCGs, and furthermore its function could be redundant with that of the highly related gene, IGR2.…”
mentioning
confidence: 75%
“…GRT1 is the second non-GRL gene in Tetrahymena DCGs to be analyzed, and in both cases gene disruption had no effect on DCG core formation or exocytosis (16). In the case of IGR1 the lack of phenotype could be potentially explained by the low abundance of the protein and also by the fact that a second, closely related gene was subsequently found to be encoded in the genome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some members of this superfamily are Protein S (2), Spherulin 3a (3,4), Streptomyces killer toxin-like protein (SKLP) (5), cargo proteins from Tetrahymena thermophila (6), AIM1 (absent in melanoma) (7), epidermis differentiation-specific proteins (8,9), yeast killer toxin WmKT (10), and Streptomyces metalloproteinase inhibitor (SMPI) (11). These members show structural similarity despite relatively low sequence identity, which reflects the functional diversity found among these proteins.…”
mentioning
confidence: 99%
“…详细的分子作用机制和功能目前尚不清楚 。随着相关研究的不断深入,在脊椎动物 的眼球晶状体中还发现了具有种属特异性的其他 类型的晶状体蛋白,如主要分布在大多数鸟类和爬 行动物中的 δ-crystallin,特异性分布在蛙和壁虎中 的 ρ-crystallin。这些种属特异的晶状体蛋白质,一 般 具 有 各 种 酶 活 性 和 辅 酶 作 用 (Wistow & Piatigorsky, 1988;Wistow, 1993;Bloemendal et al, 2004)。 目前研究表明,在眼球晶状体之外也检测到有 α、β、γ 三类晶状体蛋白的表达。非晶状体 α-晶状 体蛋白属于小热休克蛋白超家族,主要作为分子伴 侣,具有自我激活的酶活性,参与 γ-晶状体蛋白基 因的激活,与神经系统功能失调具有协同相关性 (Ganea, 2001;Narberhaus, 2002;Reddy et al, 2006)。 非晶状体 βγ-晶状体蛋白从微生物到高等哺乳动物 都有报道 (Wistow & Piatigorsky, 1988;Bhat, 2004), 包括微生物来源的应急蛋白和脊椎动物中的非晶 状体 βγ-晶状体蛋白,例如 Protein S (Nelson & Zusman, 1983), Spherulin 3a (Nelson & Zusman, 1983;Rosinke et al, 1997) , 来 源 于 四 膜 虫 Tetrahymena thermophila 的转运蛋白 Cargo proteins (Haddad et al, 2002),表皮分化专一蛋白(epidermis differentiation-specific proteins,EP37) (Takabatake et al, 1992;Wistow et al, 1995;Ogawa et al, 1997), 大蹼 铃蟾皮肤分泌物中分离得到的非晶状体 βγ-晶状体 蛋白与三叶因子复合物(βγ-CAT)的 α 亚基和哺乳动 物中的黑色素瘤缺失蛋白(absent in melanoma 1, AIM1) (Ray et al, 1997;Teichmann et al, 1998)。尽管 EP37 蛋白和 AIM1 基因参与表皮发育和肿瘤抑制, 被认为是一个潜在的肿瘤抑制基因 (Ogawa et al, 1997;Ogawa et al, 1998;Ray et al, 1997;Teichmann et al, 1998)。但是,对于脊椎动物中的非晶状体 βγ- Nelson & Zusman, 1983);细菌 Physarum polycephalum 的囊泡形成蛋 白 Spherulin 3a (Bernier et al, 1987;Wistow, 1990;Kretschmar et al, 1999) ; 细 菌 Methanosarcina acetivorans 的 M-crystallin (Barnwal et al, 2006);细 菌 Streptomyces nigrescens TK-23 的 SMPI (streptomyces metalloproteinase inhibitor) (Ohno et al, 1998);从土壤细菌培养物 Streptomyces F-287 上清 中 分 离 得 到 的 蛋 白 SKLP(streptomyces killer toxin-like protein) (Ohki et al, 2001) ; Williopsis mrakii 酵母的 WmKT(killer toxin from the yeast Williopsis mrakii) (Antuch et al, 1996)…”
unclassified